(untitled) (In situ, 2024)
The tumulus on Lokva is located at 1467 masl, in the area of the Biokovo peak plateau. Archaeological research revealed 3 burials. The earliest one was found with the remains of a ceramic vessel, which is specific to the Early Bronze Age Cetina cultural group in terms of shape and decoration. Stone burial structure of mentioned grave was used secondarily for subsequent burials in the 14th and 15th centuries.